Three-Dimensional Measurement of Femoral Neck Anteversion and Neck Shaft Angle. Issue 1 (January 2015) - Sangeux, Morgan; Pascoe, Jessica; Graham, H. Kerr; Ramanauskas, Fiona; Cain, Tim
<x xml:space="preserve">Abstract</x> Abstract We present a three-dimensional measurement technique for femoral neck anteversion and neck shaft angles which do not require alignment of the femoral and scanner axes. Two assessors performed the measurements on 11 patients (22 femurs). Repeatability between assessors was 2.7 degrees for femoral neck anteversion and 4.8 degrees for neck shaft angle. Measurements compared with an alternative single slice method were different by 2 degrees (3 degrees) in average. The method was repeatable and appropriate for clinical practice.